Edukasi Bahaya Kosmetik Ilegal di Desa Plesungan Kecamatan Gondangrejo Kabupaten Karanganyar Jawa Tengah: Education on the Danger of Illegal Cosmetics in Plesungan Village, Gondangrejo District, Karanganyar District, Central Java - Puspitasari, Lia; Larasati, Rizky Dwi; Astuti, Rini Budi; Prabowo, Imam; Sari, Putri Kharisma Novita; Fatimi, Hana Anisa; Nugraha, Akbar Eka; Pribadi, Fitrawan Hernuza (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Cosmetics are one of the products to improve appearance which are increasingly widely used in Indonesia. However, the large number of cosmetic uses is not in line with the quality. In recent years, Badan Pengawas Obat dan Makanan (BPOM) has noticed an increase in the spread of illegal cosmetics in Indonesia. Educational videos are one practical medium that can be used to promote the dangers of illicit cosmetics. This community service program aims to increase public understanding of the dangers of illegal cosmetics circulating on the market. Community service activities are created by creating educational materials and videos that are disseminated to the public directly or via social media. So that through this educational video, the public can understand it well. The activities then looked at the public's initial level of understanding of the dangers of cosmetics by conducting a pre-test. After that, the videos and materials that had been prepared were shown, and then the public's knowledge increased through the post-test. From the results of the pre-test and post-test, it was found that public understanding of the dangers of cosmetics increased by 17.1%. So it can be concluded that this service activity successfully educated the community.